ChemInform Abstract: Reaction of 4‐[2‐(Arylmethylidene)hydrazinylidene]cyclohexa‐2, 5‐dienones with Aromatic Amines. Issue 16 (22nd April 2014) - Murashevich, B. V.; Burmistrov, K. S.; Toropin, N. V.
Abstract The reaction can regarded as 1, 8‐addition starting with direct nucleophilic attack by amino nitrogen of amines (II) on CH=N carbon.